2010
DOI: 10.1080/13664530.2010.494495
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the nature of feedback given to pre‐service English teachers during their practice teaching experience

Abstract: This study seeks to understand how university supervisors and cooperating teachers approach giving feedback during the practice teaching experience to preservice English language teachers and the nature of feedback they give through post-lesson conferences and written evaluations. The data for the study come from field notes of classroom observations, post-lesson conferences between student teachers and university supervisors, and student teachers and cooperating teachers, written evaluation sheets and documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 22 publications
1
49
1
3
Order By: Relevance
“…From social cultural theory, feedback can help to identify and correct errors and can explain misunderstandings (Orsmond & Merry, 2011). Articles from behaviourism (e.g., Auld et al, 2010;Goodman et al, 2008), cognitivism (e.g., Shute, 2008), social cultural theory (Ackan & Tatar, 2010;Brinko, 1993;Yeh & Lo, 2009) and social constructivism (Colasante, 2011;Gielen et al, 2010) indicated that feedback should be specific and clear. Others used different terms: feedback should be concrete (Brinko, 1993) consistent (Brinko, 1993;Ovando, 2005; from social cultural theory), and descriptive (Fund, 2010;Kretlow & Bartholomew, 2010; from social constructivism).…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…From social cultural theory, feedback can help to identify and correct errors and can explain misunderstandings (Orsmond & Merry, 2011). Articles from behaviourism (e.g., Auld et al, 2010;Goodman et al, 2008), cognitivism (e.g., Shute, 2008), social cultural theory (Ackan & Tatar, 2010;Brinko, 1993;Yeh & Lo, 2009) and social constructivism (Colasante, 2011;Gielen et al, 2010) indicated that feedback should be specific and clear. Others used different terms: feedback should be concrete (Brinko, 1993) consistent (Brinko, 1993;Ovando, 2005; from social cultural theory), and descriptive (Fund, 2010;Kretlow & Bartholomew, 2010; from social constructivism).…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
“…From a behaviouristic (Ochieng' Ong'ondo and Borg, 2011) and social cultural theory (Ackan & Tatar, 2010) perspective, feedback can be directive. However, Ackan and Tatar (2010) suggested that directive feedback is not appropriate and they argued that it should elicit student teachers' reflection.…”
Section: Feedback Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations